PROTOTIPE 12 SADAPAN ELEKTROKARDIOGRAF BERBASIS MIKROKONTROLER ATMEGA32U4 - , Siddiq Wahyu Hidayat, Drs. Gede Bayu Suparta, M.S., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In Indonesia, research on the manufacturing industrial standard ECG has not been well developed though healthcare industry opportunities in the country especially the heart detection tools are promising. To answer these problems, it should be designed a standard ECG 12 lead which can be produced by the domestic industry with a minimum of materials with attention to the components on the market, but with due regard to health standards. The purpose of this research was to create a 12 lead ECG design based on microcontroller ATmega32U4, making ECG reference design at an affordable price, to know how to test the performance of the ECG has been built, and determine whether the ECG that has been made already qualified performance of an ECG technically or medically. The research method consisted of three main stages, namely the first stage was the design, the second stage was construction and validation, the third stage was analysis of results. In the first stage, the design of 12 lead ECG was made with a domestic component specification. In this stage was also prepared patient simulation data from a commercial ECG as comparative data with the prototype will be built. In the second stage the entire block prototype ECG was combined into a complete system. Furthermore, the system was calibrated and validated with the data input from patient simulator. The third step was to take the data from ECG prototype and compare it with a commercial ECG. A 12 lead ECG prototype had been successfully developed. This prototype consisted of the electrodes, analog circuits, microcontroller module, and a computer program. ECG waveform frequency was same as the reference and input simulator. ECG graph from the constructed prototype had same basic shape graphs with ECG reference with differences in the detail wave parts P and T 30% higher and R 50% wider. Value of the leakage current on the grounding cable and enclosure met the specified requirements, but the leakage current at the electrode exceeded the limit on a single fault condition. From this study concluded that the prototype ECG was technically necessary repairing detailed charts for accurate diagnosis and medically improve patient safety against leakage current.